Beneficial effects of lingonberry (Vaccinium vitis-idaea L.) supplementation on metabolic and inflammatory adverse effects induced by high-fat diet in a mouse model of obesity - Ryyti, Riitta; Hämäläinen, Mari; Peltola, Rainer; Moilanen, Eeva (PLOS ONE, 2020)
Obesity is a constantly increasing health problem worldwide. It is associated with a systemic low-grade inflammation, which contributes to the development of metabolic disorders and comorbidities such as type 2 diabetes. Diet has an important role in the prevention of obesity and its adverse health effects; as a part of healthy diet, polyphenol-rich berries, such as lingonberry (Vaccinium vitis-idaea L.) have been proposed to have health-promoting effects. In the present study, we investigated the effects of lingonberry supplementation on high-fat diet induced metabolic and inflammatory changes in a mouse model of obesity. Thirty male C57BL/6N mice were divided into three groups (n = 10/group) to receive low-fat (LF), high-fat (HF) and lingonberry-supplemented high-fat (HF+LGB) diet for six weeks. Low-fat and high-fat diet contained 10% and 46% of energy from fat, respectively. Lingonberry supplementation prevented the high-fat diet induced adverse changes in blood cholesterol and glucose levels and had a moderate effect on the weight and visceral fat gain, which were 26% and 25% lower, respectively, in the lingonberry group than in the high-fat diet control group. Interestingly, lingonberry supplementation also restrained the high-fat diet induced increases in the circulating levels of the proinflammatory adipocytokine leptin (by 36%) and the inflammatory acute phase reactant serum amyloid A (SAA; by 85%). Similar beneficial effects were discovered in the hepatic expression of the inflammatory factors CXCL-14, S100A10 and SAA by lingonberry supplementation. In conclusion, the present results indicate that lingonberry supplementation significantly prevents high-fat diet induced metabolic and inflammatory changes in a murine model of obesity. The results encourage evaluation of lingonberries as a part of healthy diet against obesity and its comorbidities.